Direct Evidence for a Radial Gradient in Age of the Apple Fruit Cuticle - Si, Yiru; Khanal, Bishnu P.; Schlüter, Oliver K.; Knoche, Moritz (Frontiers in Plant Science, 2021)
The pattern of cuticle deposition plays an important role in managing strain buildup in fruit cuticles. Cuticular strain is the primary trigger for numerous fruit-surface disorders in many fruit crop species. Recent evidence indicates a strain gradient may exist within the apple fruit cuticle. The outer layers of the cuticle are more strained and thus more susceptible to microcracking than the inner layers. A radial gradient in cuticle age is the most likely explanation. Our study aimed to establish whether (or not) deposition of new cutin in a developing apple fruit occurs on the inner surface of the cuticle, i.e., immediately abutting the outward-facing epidermal cell wall. Developing apples were fed with 13C oleic acid through the skin. Following a 14-d period for incorporation, the fruit was harvested and the cuticular membranes (CMs) isolated enzymatically. The CMs were then ablated to varying extents from the inner or the outer surfaces, using a cold atmospheric pressure plasma (CAPP). Afterwards, the ablated CMs were dewaxed and the 13C contents were determined by mass spectrometry. The incorporation of 13C in the cutin fraction was higher than in the wax fraction. The 13C content was highest in non-ablated, dewaxed CM (DCM) and decreased as ablation depth from the inner surface increased. There was no change in 13C content when ablation was carried out from the outer surface. As fruit development proceeded, more 13C label was found towards the middle of the DCM. These results offered direct evidence for deposition of cutin being on the inner surface of the cuticle, resulting in a radial gradient in cuticular age—the most recent deposition (youngest) being on the inner cuticle surface (abutting the epidermal cell wall) and the earliest deposition (oldest) being on the outer surface (abutting the atmosphere).